Oliver moon and the broomstick battle - Mongredien, Sue; McCafferty, Jan (Usborne London, 2007)
Oliver is excited about entering the Junior Wizards' Obstacle Course in the annual Broomstick Olympics, but Billy Bogeywort is intent on ruining Oliver's chances of winning. Can Oliver overcome Bully's cheating tactics